Sosialisasi Manfaat Teknologi Virtual Augmented dan Virtual Reality Bagi Peningkatan Bidang Manajemen Pendidikan - Jusuf Wahyudi; Nofi Qurniati; Ricky Zulfiandry; Suwarni Suwarni; Desi Mahdalena; Wahyu Al Amar (Universitas Dehasen Bengkulu, 2023)
This Community Service (PKM) aims to advance information technology so that later students who are studying at SMKN 3 Bengkulu Tengah will get additional insight into computer science in the field of information technology such as Virtual Reality and Virtual Augmented which in everyday terms do not let many students gaptek (stuttering technology) in order to play a more role in world competition outside the school walls. The benefits of PKM activities are aimed at SMKN 3 Bengkulu Tengah students who are expected to be able to utilize and apply them to other fields of science related to the science they are studying. The results and conclusions of this PKM are that this PKM activity has educated and provided knowledge of Virtual Augmented and Virtual Reality Technology and its role in the world of education. So that students of SMKN 3 Bengkulu Tengah can better prepare themselves to become a creative, innovative and inspiring young generation in the face of technological advances.